Long Non-coding RNAs as Communicators and Mediators Between the Tumor Microenvironment and Cancer Cells - Chen, Di; Lu, Tong; Tan, Junying; Li, Hao; Wang, Qiuyue; Wei, Liangzhou (Frontiers in Oncology, 2019)
Long non-coding RNAs (lncRNAs) are a class of RNA transcripts of more than 200 nucleotides which have have limited protein coding capacity. They are critical modulators that regulate numerous biological processes in cancers through diverse mechanisms. The aberrant expression of lncRNAs is frequently associated with human cancer. Furthermore, the tumor microenvironment (TME) is composed of different cells such as cancer-associated fibroblasts (CAFs), endothelial cells and infiltrated immune cells, and all of which participate in the communication with tumor cells to affect the progression of tumor. LncRNAs are directly and indirectly involved in the crosstalk between stromal cells and tumor cells and dysregulated lncRNAs expression in these cells could drive tumorigenesis. Herein, we explore the influence of aberrantly expressed lncRNAs in the progression of tumor, clarify the critical roles of lncRNAs in the TME, summarize the crosstalk between infiltrated immune cells, CAFs, endothelial cells, and tumor cells via lncRNAs, and discuss the promise of lncRNAs as tumor diagnostic markers and therapeutic targets.